Evaluation of a learning analytics tool for supporting teachers in the creation and evaluation of accessible and quality open educational resources. (19th April 2020) - Avila, Cecilia; Baldiris, Silvia; Fabregat, Ramon; Graf, Sabine
Abstract: The learning analytics (LA) field seeks to analyze data about students' interactions, and it has been applied in the development of tools for supporting both learning and teaching processes. Recent research has paid attention on how LA may benefit teachers in the creation of educational resources. However, most of the research on LA solutions is carried out to support teachers in analyzing students' behavior data collected as they interact with virtual learning environments. While solutions to support teachers in different virtual learning and teaching contexts have become important, to date little research has been done on how LA solutions can help teachers to create and evaluate Open Educational Resources (OERs). This study aims at presenting the evaluation of a LA tool for supporting teachers in the creation and evaluation of accessible and quality OERs considering that both processes fall within the competences that teachers can acquire and strengthen by participating as authors (creation) and evaluators (evaluation) of OERs. The study was conducted with Colombian teachers and the results obtained highlight the positive effect the tool had on the teachers' acquisition of the competences and the positive attitude they had toward using the tool.